2022
DOI: 10.1111/jpi.12798
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin treatment improves ventricular conduction via upregulation of Nav1.5 channel proteins and sodium current in the normal rat heart

Abstract: Melatonin treatment was reported to reduce the risk of cardiac arrhythmias, and crucial for this antiarrhythmic action was the effect of melatonin on activation spread. The aim of the present study was evaluation of the mechanisms of this activation enhancement. Experiments were performed in a total of 123 control and melatonin-treated (10 mg/kg, daily, for 7 days) male Wistar rats. In epicardial mapping studies (64 leads, interlead distance 0.5 mm) in the anesthetized animals, activation times (ATs) were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…For the elucidation of the acute antiarrhythmic effect of melatonin, its electrophysiological targets should be identified. Our study in the chronic model of melatonin treatment [28] demonstrated that conduction enhancement was caused by the melatonin-related increase in the sodium channel protein expression (Scn5a/Nav1.5) resulting in the augmentation of the sodium current INa. We tested INa in the present study, having in mind the hypothesis that similar effects might be induced by acute melatonin application.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…For the elucidation of the acute antiarrhythmic effect of melatonin, its electrophysiological targets should be identified. Our study in the chronic model of melatonin treatment [28] demonstrated that conduction enhancement was caused by the melatonin-related increase in the sodium channel protein expression (Scn5a/Nav1.5) resulting in the augmentation of the sodium current INa. We tested INa in the present study, having in mind the hypothesis that similar effects might be induced by acute melatonin application.…”
Section: Discussionmentioning
confidence: 66%
“…The procedure of epicardial mapping has been described elsewhere [28,55]. In brief, in 12 animals of the melatonin group (MEL), 10 animals of the luzindole group (LUZ), 11 animals of melatonin + luzindole (MEL + LUZ) group, and 17 animals of the control group (CONTROL), unipolar electrograms were recorded in the left ventricle (LV) using a 64-lead array.…”
Section: Epicardial Mappingmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the antiarrhythmic and electrophysiological effects of melatonin have been assessed only in animal experimental models [ 13 , 14 , 15 , 18 , 21 , 22 , 23 , 24 , 25 ]. In our previous study, we analyzed the intramyocardial electrograms in the experimental porcine model, and melatonin demonstrated the prevention the early ischemic VF via reduction in conduction delay in the border myocardium [ 15 ].…”
Section: Introductionmentioning
confidence: 99%